The Effect of Social Support and Batak Values on Self-Acceptance of Fathers Who Have Children with Special Needs - Ervina Marimbun Rosmaida Siahaan; Karina Meriem Beru Brahmana; Nenny Ika Putri Simarmata; Grace Aqueena (Journal of Educational, Health and Community Psychology, 2023)
Having children is a blessing. Because the case may be different for children born with special needs conditions. What comes is emotional feelings such as anger, sadness, disappointment, and not accepting it. In this condition, the father has a significant impact on the development of the child. However, due to the child's condition, it becomes a challenge for the father to adjust. The purpose of this study was to determine the effect of social support and Batak values on self-acceptance in fathers who have children with special needs (ABK). The research method used is a quantitative approach using data analysis techniques, namely multiple linear regression analysis by applying SPSS 22 with independent variables, social support and Batak values, and dependent variables, namely self-acceptance. The study sample consisted of 44 fathers who had ABK, using purposive sampling techniques.  The data were analyzed using multiple linear regression with the application of SPSS 22.  The results showed that social support and Batak values negatively affect the acceptance of fathers who have children with special needs, which means that the higher the social support and Batak values, the lower the acceptance of fathers. Keywords: Self-acceptance, Social Support, Batak Values, Children with Special Needs